Diagnostic value of a comprehensive, urothelial carcinoma–specific next‐generation sequencing panel in urine cytology and bladder tumor specimens. Issue 7 (4th February 2021) - Sun, Tong; Hutchinson, Lloyd; Tomaszewicz, Keith; Caporelli, Mandi‐Lee; Meng, Xiuling; McCauley, Kathleen; Fischer, Andrew H.; Cosar, Ediz F.; Cornejo, Kristine M.
Abstract : Background: Urine cytology can reliably diagnose high‐grade urothelial carcinoma (HGUC) but not low‐grade urothelial carcinoma (LGUC), and a more sensitive test is needed. Previously, a pilot study highlighted the possible diagnostic utility of next‐generation sequencing (NGS) in identifying both LGUC and HGUC in urine cytology specimens. Methods: Twenty‐eight urine ThinPrep cytology specimens and preceding or subsequent bladder tumor biopsy/resection specimens obtained within 3 months were included in the study (LGUC, n = 15; HGUC, n = 13). A customized, bladder‐specific NGS panel was performed; it covered 69 frequently mutated or altered genes in urothelial carcinoma (UC) that were reported by The Cancer Genome Atlas and the Catalogue of Somatic Mutations in Cancer. Results: The sequencing results were compared between the urine cytology specimens and the corresponding bladder tumor biopsies/resections. TP53 was the most frequently identified mutation in HGUC cases (11 of 13 [85%]). PIK3CA and KDM6A were the most frequently identified mutations in LGUC: they occurred in 7 of 15 cases (47%) and in 6 of 15 cases (40%), respectively. Additional frequent mutations identified in the panel included ARID1A (n = 5), EP300 (n = 4), LRP1B (n = 3), ERBB2 (n = 2), STAG2 (n = 2), FGFR3 (n = 3), MLL (n = 2), MLL3 (n = 2), CREBBP1 (n = 1), RB1 (n = 1), and FAT4 (n = 1). Overall, the concordance between the cytology and surgical specimens was 75%. The sensitivity and specificity for identifying mutations in urine cytology specimens were 84% and 100%, respectively. Conclusions: A bladder‐specific NGS panel increases the sensitivity and specificity of urine cytology's diagnostic utility in both low‐ and high‐grade tumors and may serve as a noninvasive surveillance method in the follow‐up of patients with UC harboring known mutations. Abstract : A comprehensive, urothelial carcinoma (UC)–specific next‐generation sequencing (NGS) panel successfully identifies both low‐ and high‐grade tumors in urine cytology samples. Therefore, urine specimens have the potential to replace tissue as a substrate for NGS analysis in both the detection and surveillance of UC.